ANALISIS DAMPAK PROGRAM PELATIHAN DAN PENGEMBANGAN TERHADAP KEMAMPUAN KERJA PEGAWAI (Studi Pada Bagian Protokol Sekretariat Daerah Kabupaten Kutai Timur - Rudianto, Apul (PREDIKSI, 2015)
ABSTRACTÂ This study aims to determine whether the Training and Development Program has a positive influence on Improving Employee Work Capability In Part Protocol Secretariat of Kabupaten Kutai Timur.The results showed that there is a positive and significant relationship between the variables and Development Training Program with variable Employee Work Capability In Part Protocol Secretariat of East Kutai Regency. It can be seen from the results of statistical test in which the correlation coefficient (r) is equal to 0.672, which means there is a strong relationship between the two variables.The results showed also that there is a strong relationship between the variables of Training and Development with variable Employee Work Capability. This means that the significant impact of the variable Training and Development Program for Employee Work Capability Protocol Section Regional Secretariat of East Kutai. Thus it can be said that the goal of this research can be achieved, the problems can be solved and the hypothesis can be proven.Â